Application of Geographic Information System (GIS) in Soil Erosion Prediction: A Case Study of the Sg. Hijau Watershed, Fraser's Hill, Pahang - Ng, Anastasia Suan Kim (2003)
A study was conducted to assess soil erosion using Geographical Information System (GIS) and Universal Soil Loss Equations (USLE) for the Sg. Hijau watershed. The study area, located in Fraser's Hill, Pahang is 1.5 km2 in size and lies between 1060 and 1350 m a.s.l. A GIS software, ARC/INFO version 3.4 was used to develop the database. Analysis was carried out using the ArcView Spatial Analyst Version 1.1 and ArcView 3D Analyst. Results obtained show that about 48% of the Sg. Hijau catchment falls under the slope gradient of 12°_25° while 26% of the area under the slope of more than 25°. Four empirical methods based on the applications of erosivity were used for soil erosion computation. They were from Roose (1975), Balamurugan (1990), Morgan (1974) and rainfall of more than 25 mm/hr adopted in this study. By comparison, Roose generated the highest erosion rate with 1.757 t/ha/yr followed by Balamurugan with 0.685 t/ha/yr, 25 mm/hr with 0.567 t/ha/yr and lastly, Morgan with 0.532 t/ha/yr. Erosion rates of less than 1 t/ha/yr were computed for most of the area in the study watershed: soil erosion rates ranged from 0.363 to 0.642 t/ha/yr. The results obtained were also comparable to measured soil loss from erosion plots in other studies under similar conditions. Most studies have shown that erosion seldom exceeds 1 t/ha/yr under forest conditions. This study showed that soil erosion rates could be calculated using USLE within the GIS environment. Apart from employing GIS as an easy-to-use database and toolkit for modeling, GIS techniques could be used to assess the uncertainty and validity of spatial erosion models. The use in catchment hydrological and erosion modeling offers considerable potential.